New ways in fostering self-regulated learning at university: how effective are web-based courses when compared to regular attendance-based courses? - Beek, Sophie van der; Bellhäuser, Henrik; Karlen, Yves; Hertel, Silke (Zeitschrift für pädagogische Psychologie, 2020)
. Self-regulated learning is essential for studying successfully at university. However, students often show deficits in their ability to learn in a self-regulated way. Consequently, it has become crucial to foster students' self-regulated learning at university. The effectiveness of such courses has primarily been investigated in regular class contexts that require physical attendance. However, web-based course formats are currently gaining in importance. Web-based courses have several advantages (e. g., that students can decide when and where they want to study). The question of whether a web-based course is as effective as an attendance-based one has yet to be answered. In a randomized intervention study (N = 186 university students) with two different treatments (attendance-based and web-based courses), it was investigated whether students in the web-based format profited to the same extent as students in the attendance-based course. Kirkpatrick's model was implemented for evaluation. The results showed that the students were very satisfied with both course formats, self-regulated learning was considered useful for studying, and the subjective and objective increases in learning were high. Furthermore, the results showed that self-regulated learning can be fostered in the web-based course as effectively as in the attendance-based course.